2017
DOI: 10.3892/ol.2017.6269
|View full text |Cite
|
Sign up to set email alerts
|

Significance of E-cadherin and CD44 expression in patients with unresectable metastatic colorectal cancer

Abstract: Abstract. The loss of adhesion molecules is reported to be associated with tumor invasion and metastasis in numerous types of cancer. Epithelial (E)-cadherin is an important molecule for cell-to-cell adhesion, while cluster of differentiation (CD)44 is an important molecule for cell-to-extracellular matrix adhesion. The focus of the present study was to evaluate the significance of the expression of E-cadherin and CD44 in patients with the unresectable metastatic colorectal cancer (CRC) who are undergoing pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
8
15
0
Order By: Relevance
“…Epithelial-mesenchymal transition (EMT) contributes to the invasion and migration of cRc (33). E-cadherin and N-cadherin are important in EMT of cRc (34,35). The results of the current study demonstrate that E-cadherin was upregulated after ANXA9 inhibition, whereas no obvious variation was verified in N-cadherin.…”
Section: Discussionmentioning
confidence: 56%
“…Epithelial-mesenchymal transition (EMT) contributes to the invasion and migration of cRc (33). E-cadherin and N-cadherin are important in EMT of cRc (34,35). The results of the current study demonstrate that E-cadherin was upregulated after ANXA9 inhibition, whereas no obvious variation was verified in N-cadherin.…”
Section: Discussionmentioning
confidence: 56%
“…81 Combined assessment of E-cadherin and CD44 in colorectal cancer has been shown to have a higher prognostic value than isolated evaluation of single markers. 29,82 The pathways of EMT induction and stemness differ by MSI status. Twist1 induced EMT and CD44 via AKT/GSK-3beta/beta-catenin and AKT/NF-kappaB pathways in MSS cells, while only the beta-catenin pathway was activated in MSI colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 A combined low expression of E-cadherin and CD44 is associated with decreased overall survival in patients with metastatic colorectal cancer. 29 Given these prognostic trends, associations between the listed factors might be hypothesized. However, few studies have tried to assess directly the mutual relationships between inflammation, EMT, stem cell differentiation and the expression of MMR proteins in the same cohort of colorectal cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of E-cadherin is thought to be one of the first steps in metastasis, playing critical roles in tumor metastasis [21,[31][32][33]. Recent reports have shown that a decrease in E-cadherin is strongly associated with metastasis and poor clinical prognosis and suggested that targeting E-cadherin could be a promising therapeutic approach for metastatic CRC [34]. In this study, we showed that knockdown of DAXX can significantly decrease E-cadherin both at the transcriptional level and the translational level.…”
Section: Discussionmentioning
confidence: 99%